Australia and Taiwan : Bilateral Relations, China, the United States, and the South Pacific. - Atkinson, Joel (BRILL, 2012)
In Australia and Taiwan, Joel Atkinson examines the intriguing and important Australia-Taiwan relationship. He covers its history, the role of Taiwan in Australia's relations with China and the US, and bilateral issues such as ministerial visits and the South Pacific.